The Importance of Inspiratory Maneuver for Benign Laryngeal Lesions - Costa,Marília Batista (2020)
Abstract Introduction Inspiratory maneuver corresponds to a simple method used during videolaryngoscopy to increase characterizations of laryngeal findings, through the movement of the vocal fold cover and exposure of the ligament, facilitating its evaluation. Objective To evaluate the increase in diagnosis of benign laryngeal lesions from the usage of inspiratory maneuvers during videolaryngoscopy in patients with or without vocal complaints. Methods A cross-sectional study performed from March 1 to July 1, 2018, in the Laryngology sector of a tertiary hospital. The age of the patients varied from 18 to 60 years old. They were divided into two groups, symptomatic and asymptomatic vocals, and evaluated through videolaryngoscopy together with inspiratory maneuvers. The exams were recorded and later evaluated by three trained laryngologists who determined the laryngeal lesions before and after the inspiratory maneuver. Results There were 60 patients in this sample, 41 of which were vocal symptomatic and 19 asymptomatic. The majority was female and the main complaint was about dysphonia. Before the inspiratory maneuver, the most observed lesions in both groups were chronic laryngitis, followed by vascular dysgenesis. After the inspiratory maneuver, sulcus vocalis was the most frequent additional finding. Conclusion With the inspiratory maneuver, it was possible to increase the identification of structural lesions in the vocal fold, and the most frequent lesion in patients with or without vocal complaints was sulcus vocalis.